Service Quality, Promotions, and Price Breaks All Have An Impact on Consumers Who Purchase Interest (Alfamart dr. Soetomo jl. Dr. Soetomo, Payaman, kec. Nganjuk, Nganjuk District, East Java) - Aji, Bagus; Yap, Nonni (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
The purpose of this study is to ascertain how consumer interest in buying at Alfamart, Dr. Soetomo Jl., Dr. Soetomo, Payaman, District Nganjuk, Nganjuk Regency, East Java, is influenced by price discounts, promotions, and service quality. Eighty samples from Alfamart Jl. Dr. Soetomo, Payaman, District customers were used. Nganjuk, Regency of Nganjuk, East Java. This study employed a quantitative approach, collecting data through the distribution of questionnaires. This study uses SPSS version 24 for analysis. Statistical analysis is used to process the data, including tests for validity, reliability, classical assumptions, multiple linear regression, hypothesis testing, and coefficient of determination analysis. The analysis's findings indicate that the multiple linear regression test's outcomes are Y= 6.976 + 0.282 (X1) + 0.370 (X2) + 0.346 (X3). Service Quality has a strong and partial positive influence on Purchase Interest, with a significant value of 0.000 < 0.05 and a value of tcount (3.662) > ttable (1.9916). Promotion has a strong and partial positive influence on Purchase Interest, as evidenced by a significant value of 0.001 < 0.05 and a value of tcount (3.507) > ttable (1.9916). The results of the F test indicate that Service Quality, Promotion, and Price Discounts have a significant and positive effect. Promotion has a partial and significant positive influence on Purchase Interest with a value of tcount (3.424) > ttable (1.9916) and a significant value of 0.001 < 0.05. H0 is rejected and Ha is accepted with a value of Fcount 16.548 > Ftable 2.72 and a significant value of 0.000 < 0.05.